Exposures to near-to-maximal speed running bouts during different turnarounds in elite football: association with match hamstring injuries - Buchheit, Martin; Settembre, Maxime; Hader, Karim; McHugh, Derek (Biology of Sport, 2023)
To describe the occurrence of near-to-maximal sprinting speed (near-to-MSS) running bouts during training and hamstring injuries during the consecutive match of the same turnaround in elite football (soccer). Retrospective data from 36 team-seasons (16 elite teams performing in top European leagues) were analyzed (627 players, 96 non-contact time loss match hamstring injuries). We described 1) the occurrence of > 85%, > 90% or > 95% MSS exposures during training within each turnaround and match hamstring injuries and 2) whether the above-mentioned injury occurrences differed depending on the day(s) of the turnarounds (i.e., the period separating two consecutive matches, which is generally from 3 to 8 days) when these speed exposures occurred. The longer the length of the turnarounds and the lower the speed thresholds, the greater the number (and proportion) of near-to-MSS exposures (e.g., 18%, 45% and 72% of turnarounds with > 85% runs for 3, 5 and 7 turnarounds, respectively). For half of the turnarounds examined, there were no match hamstring injuries when players were exposed to running bouts > 95% MSS during training (e.g., injury rates: 0; CI: 0–15). Injuries still occurred during 85% of the turnarounds when there were no or lower relative speed exposures (i.e., > 85 or > 90%, injury rates: 2–5, CI: 0 6). Finally, irrespective of the turnaround length, there were no match hamstring injuries when > 95% MSS exposures occurred at D-2, while in contrast, injuries still happened when players were not exposed at all, or when these exposures occurred at D-3 and/or earlier within the turnaround. While the present observational study design precludes the examination of causal relationships, the programming of > 95% MSS exposures at D-2 may help mitigate match hamstring injury occurrences in elite football.